2022
DOI: 10.3390/plants11192561
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Efficiency of the Accumulation of Recombinant Proteins in Plant Cells: The Role of Transport Signal Peptides

Abstract: The problem with increasing the yield of recombinant proteins is resolvable using different approaches, including the transport of a target protein to cell compartments with a low protease activity. In the cell, protein targeting involves short-signal peptide sequences recognized by intracellular protein transport systems. The main systems of the protein transport across membranes of the endoplasmic reticulum and endosymbiotic organelles are reviewed here, as are the major types and structure of the signal seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 213 publications
0
3
0
Order By: Relevance
“…The presence of targeting peptides is a critical aspect in recombinant protein design as it determines subcellular compartments and can affect yield [ 2 ]. Here we found that the bacterial protein PmoB, present in methanotroph bacteria, localises to mitochondria when recombinantly expressed in plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of targeting peptides is a critical aspect in recombinant protein design as it determines subcellular compartments and can affect yield [ 2 ]. Here we found that the bacterial protein PmoB, present in methanotroph bacteria, localises to mitochondria when recombinantly expressed in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are an attractive platform for the production of recombinant proteins due to benefits such as cost-effectiveness, ease of scalability and the lack of potential contaminants present in other systems, such as animal viruses or bacterial toxins [ 1 , 2 ]. Targeting proteins to specific compartments within the plant cell is a strategy often utilised to ensure correct functioning of the recombinant system or increase yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation